Insights into the Design of Anti-inflammatory Agents Against Arthritis Based on Molecular Docking - Asghar, Saira; Farid, Faryal; Mushtaq, Aqsa; Iqtadar, Rabia; Sadaf, Farzana (Journal of Medical Science, 2026)
Introduction. Arthritis encompasses a heterogeneous group of chronic disorders, notably rheumatoid arthritis (RA) and osteoarthritis (OA), which differ mechanistically yet converge on persistent inflammation and progressive cartilage destruction. These states are mediated by overlapping inflammatory cascades, including cyclooxygenases (COX), lipoxygenases (LOX), nuclear factor-κB (NF-κB), TNF- and IL-6 cytokines, and subsequent JAK/STAT signalling. Although numerous therapeutic strategies have been developed, existing therapies are still hampered by toxicity, slower effects, or an inability to control the disease, due to a failure to counter pathway redundancy in molecular design.Material and methods. A structured literature survey was conducted using PubMed, Scopus, Web of Science, and Google Scholar to identify peer-reviewed studies on molecular docking-guided anti-inflammatory drug design for arthritis-related targets. The relevant studies were assessed for the suitability of the target, docking process, validation method, key ligand-protein interactions, and correlation with experimental anti-inflammatory potential.Results. The review critically analyses docking-guided studies in natural products, synthetic small molecules, and biologically inspired inhibitors, but especially aims to determine the rich structure-activity relationship (SAR) principles rather than docking scores. The main lessons involve the role of conserved binding poses, regulated molecular flexibility and target selectivity.Conclusions. The future lies in combining docking, molecular dynamics, ADMET forecasting, and multi-target design techniques to develop sustainable arthritis therapeutics.
Keywords: molecular docking; anti-inflammatory agents; arthritis; structure-activity relationship (SAR)